2021
DOI: 10.1002/adfm.202106846
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT:PSS‐Free Polymer Non‐Fullerene Polymer Solar Cells with Efficiency up to 18.60% Employing a Binary‐Solvent‐Chlorinated ITO Anode

Abstract: Despite the tremendous development of different high-performing photovoltaic systems in non-fullerene polymer solar cells (PSCs), improving their performance is still highly demanding. Herein, an effective and compatible strategy, i.e., binary-solvent-chlorinated indium tin oxide (ITO) anode, is presented to improve the device performance of the state-of-the-art photoactive systems. Although both ODCB (1,2-dichlorobenzene) solvent-and ODCB:H 2 O 2 (hydrogen peroxide) co-solvent-chlorinated ITO (ITO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 56 publications
(86 reference statements)
0
31
0
Order By: Relevance
“…23) and N3, 24 have elevated the rapid development of OPVs to a higher level. Recently, many excellent studies on polymer based OPVs were reported with a PCE over 17.5%, [25][26][27][28][29][30] and an exciting value of 19% has been achieved by Hou's group. 31 Very recently, Hou's group reported a PCE of 17% in SMPVs enabled by nanoscale phase separation with a hierarchical branched structure.…”
Section: Introductionmentioning
confidence: 99%
“…23) and N3, 24 have elevated the rapid development of OPVs to a higher level. Recently, many excellent studies on polymer based OPVs were reported with a PCE over 17.5%, [25][26][27][28][29][30] and an exciting value of 19% has been achieved by Hou's group. 31 Very recently, Hou's group reported a PCE of 17% in SMPVs enabled by nanoscale phase separation with a hierarchical branched structure.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly recently, Min et al reported simple and effective methodology to improve the performance of HTL-free OSCs (Figure 15). [95] They treated the ITO glass with ODCB:H 2 O 2 cosolvent under UV irradiation, which resulted in obtaining highperformance ITO-Cl anodes. The surface chlorination treatments increased the WF of ITO electrode without reducing the conductivity.…”
Section: Inorganic Hole Transporting Layersmentioning
confidence: 99%
“…Chemistry-A European Journal Reproduced with permission. [95] Copyright 2021, Wiley-VCH. Reproduced with permission.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…[1,2] Over the past decades, the utmost endeavors have been devoted to modulating the structural and optoelectronic properties by designing new organic semiconductors, [3][4][5] controlling the morphology of photoactive layer via additives and various post-treatments, [6][7][8] maximizing the harvest of light by using ternary or tandem devices, [9][10][11][12][13][14][15][16][17] improving the extraction of electrons and holes by interfacial modification. [18][19][20] With these efforts, PSCs have witnessed rapid progress, the cutting-edge PSCs have delivered over 18% power conversion efficiencies (PCEs) (Table S1, Supporting Information), [7,8,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and there still has much space to further improvement. As is well-known, simultaneously improving the open-circuit voltage (V oc ), short-circuit current density (J sc ), and fill factor (FF) is essential to maximize the PCE of PSCs.…”
Section: Introductionmentioning
confidence: 99%